2017
DOI: 10.1158/1535-7163.mct-17-0400
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-720 Regulates E-cadherin–αE-catenin Complex and Promotes Renal Cell Carcinoma

Abstract: MicroRNAs are implicated in regulating cancer progression and metastasis. Here we show that miR-720 is positively associated with renal cell carcinoma (RCC). Elevated levels of miR-720 were observed in a panel of RCC cell lines and clinical tissues compared to non-malignant cell line and normal samples. Loss of miR-720 function inhibited proliferation, migration and invasion and induced apoptosis in RCC cell lines in vitro and repressed tumor growth in xenograft mouse model. Conversely, gain of miR-720 functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In fact, evidence shows that reduced E-cadherin is correlated with β-catenin expression and poor prognosis of renal RCC; and, E-cadherin prevents β-catenin translocation from membrane to cytoplasm, suppressing wnt/β-catenin signaling [16]. A recent study showed that inhibition of E-cadherin-α/E-catenin complex by miR-720 promoted RCC [17], indicating a preventive role of E-cadherin in RCC. In the fibrotic kidney, loss of E-cadherin, which is a marker for epithelial cells, and gain of α-SMA expression, the marker for myofibroblasts, is a key process in myofibroblast transdifferentiation from epithelial origin [18].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, evidence shows that reduced E-cadherin is correlated with β-catenin expression and poor prognosis of renal RCC; and, E-cadherin prevents β-catenin translocation from membrane to cytoplasm, suppressing wnt/β-catenin signaling [16]. A recent study showed that inhibition of E-cadherin-α/E-catenin complex by miR-720 promoted RCC [17], indicating a preventive role of E-cadherin in RCC. In the fibrotic kidney, loss of E-cadherin, which is a marker for epithelial cells, and gain of α-SMA expression, the marker for myofibroblasts, is a key process in myofibroblast transdifferentiation from epithelial origin [18].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are master gene regulators that may silence genes at the post-transcriptional level via transcript degradation or translational repression. miRNAs are extensively implicated in fundamental biological processes and aberrant microRNA profiles have been reported in various cancers including RCC [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, six chromosomes presented CNVs involving genes encoding for proteins, miRNAs (short no‐coding RNAs conformed by 20‐25 nucleotides), or lncRNAs (long no‐coding RNAs constituted by ~200 nucleotides) involved in the regulation of gene expression. The potential of these both kind of RNAs to modulate gene expression is being extensively described . These molecules regulate gene expression finely, but their perturbed activity can disturb the normal genome behaviour and promote pathological conditions …”
Section: Discussionmentioning
confidence: 99%